A atuação do Ministério Público no controle das políticas públicas - Campanella, Fabiana Leonardi (2019)
This work has as its theme the Public Prosecution Service in the control of Public Policies, having as initial study the process of conquering constitutional, social rights and the legal formation of diffuse and collective rights throughout history and social, political and juridical changes. In order to protect these rights judicially, it has been discussed the possibility of demanding from the State, the promotion of these rights when it is omitted, without violating the harmony between the three judiciaries, or interferes in the administrative discretion, since they are fundamental rights protected by stony clauses, with minimum normative density and immediate application, besides not being the option of the administrator the choice to prove them or not, having only a margin of freedom as to the means by which meet the social demands. However, this charge from the Public Authorities must be done within parameters, aiming to protect rights that make up an existential minimum, observing budgetary funds and always seeking a reasonable decision. It is hoped that the rights can be accessible to everyone, with public policies being the appropriate means for the realization of these rights, the consolidation of participatory citizenship and the reduction of social inequality. Finally, the Public Prosecutor's Office is addressed, through public civil action and specific protection, as well as the civil inquiry, term of adjustment of conduct and recommendations, protecting diffuse and collective and social rights, always in the objective of providing better quality of life for people, building a more egalitarian society and valuing democracy